The application of critic-topsis method in solving the material handling equipment selection problem / Nurul Anis Yazid ... [et al.] - Yazid, Nurul Anis; Sabtu, Nurul Izza; Azmiral, Nur Umairah Syahirah; Mahad, Nor Faradilah (Universiti Teknologi MARA, 2023)
Material handling equipment (MHE) is mechanical equipment required to transport materials or products between places. Selecting the best MHE is a crucial aspect of every industry due to a large amount of capital involved in the process. The idea behind Multi-Criteria Decision Making (MCDM) is it can address and deal with conflicting parts in the MHE selection process. The Criteria Importance Through Intercriteria Correlation (CRITIC) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods are proposed in this study to solve the MHE selection problem. This study aims to solve the MHE selection problem using the CRITIC-TOPSIS method. The CRITIC method is used to compute the criteria weights, while the TOPSIS method is applied to determine the ranking of MHE alternatives. Based on the findings, the ranking order for criteria is C = R> PR > AP > OSR > LCC > ETO = AV = AC > FIM > DIS. Meanwhile, the ranking order for the alternatives is Electric Pallet Truck > Hydraulic Pallet Truck > Hand Pallet Truck > Semi Electric Pallet Truck > Hydraulic Hand Pallet Truck. Of the five options of MHE, Electric Pallet Truck is the best option when using the CRITIC-TOPSIS method. In conclusion, the hybridization of the CRITIC-TOPSIS method is successfully used to solve the MHE selection problem.